Characteristics and Dispersion Model of Wastewater PT Kayu Lapis Indonesia, Kendal, Central Java - Rizqi Rizaldi Hidayat; Irwan Harun; Eddiyanto Eddiyanto; Isnaini Prihatiningsih; Ardiansyah Farabi (Politeknik Negeri Batam, 2023)
PT. Kayu Lapis Indonesia (PT KLI) is a company engaged in the forestry sector, particularly in wood processing. Production activities at PT KLI produce wastewater that is treated and discharged into the sea, and then spreads following ocean currents. This study aimed to analyze the characteristics of wastewater produced by PT KLI and predict the distribution pattern of the waste. The characteristics of the wastewater and seawater were obtained through in situ measurements and sampling, which were analyzed in the laboratory. The distribution pattern of wastewater discharge was modeled using the pollutant model from the hydrodynamic model results around the water. The characteristics of the PT KLI wastewater were dominated by parameters such as pH, biological oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS), and total ammonia. The wastewater was processed in a Wastewater Treatment Plant (WWTP) until all the parameters met predetermined standards before being discharged into the ocean. The model results show that wastewater tends to move westward both at high tide in the west and east monsoons and at low tide in the west and east monsoons, with little movement to the east.